Effects Of Principals’ Professional Development Practices On Teachers’ Job Performance In Public Secondary Schools In Kathiani Sub-County - Mutua, Mary Mbithe; Koech, Peter Kibet; Kimiti, Richard Peter (International Journal of Innovative Research and Advanced Studies (IJIRAS), 2022)
Professional development aims to train teachers after completing pre-service studies, by continuously developing knowledge and skills of teachers. Professional development practices help in grooming teachers for achieving better performance and, at the end, making their tasks interesting. The purpose of the study was to examine the effect of principals’ professional development practices on teachers’ job performance in public secondary schools in Kathiani SubCounty. The study utilized a descriptive research design. The target population consisted of 32 principals and 107 teachers who were drawn from the 32 public secondary schools in the Sub-County. Stratified random sampling was used to sample the teachers and a census to select all the principals. Questionnaires and interviews were used as data collection instruments. To ascertain the validity and reliability of the data collection instruments, a pilot study was carried out where a sample of 10% of the targeted population was used. The data collected was both quantitative and qualitative in nature. Quantitative data was analyzed through descriptive statistics inferential statistics. The descriptive statistics included frequencies and percentages while the inferential statistics included the Spearman-Brown correlation. The Statistical Package for Social Sciences (SPSS) version 27 was utilized in running the analysis. The quantitative data was presented in form of pie charts, bar graphs and tables. On the other hand, qualitative data was analyzed using content analysis and was presented in continuous prose. The study findings show that principals’ professional development practices and teachers’ job performance have a positive and significant relationship. These are reflected by the feedback from the teachers and principals. The principal professional development practices that improved teacher job performance are identifying the specific areas requiring re-training for teachers, organizing in-service trainings for teachers to attend, inviting TSC and MOEST officers for positive evaluation of teachers, directing HODs to evaluate teachers in their departments, mentoring teachers to improve in their profession, facilitating for teachers to attend training by KEMI, and facilitating teachers to train as national examiners. The study recommended that the Ministry of Education with the help of school principals should introduce capacity building programmes outside the school calendar - during the holidays and or weekends to help the teachers bond amongst them and also break the monotony of always being in school. This would help improve teacher job performance.
Keywords: Principals’ Professional Development Practice; Teacher Job Performance; Public Secondary School